Analisis kandungan artemisinin pada kultur tunas Artemisia annua L. dengan lima karakter morfologi yang berbeda - Tri Muji Ermayanti; Erwin Al Hafiizh; Aryanti Aryanti; Lenny Sutedja (Universitas Atma Jaya Yogyakarta, 2005)
Artemisia annua L. is a medicinal plant that has an antimalarial drug againts Plasmodium falciparum strains which are resistant to traditional drugs such as quinine and chloroquine. This plant contains artemisinin as major compounds found on its leaves. Aim of the research was to analyze the artemisinin content of shoot culture of A. annua which has five different in leaf morphologies (Morphology type A, B, C, D and E). Previous investigation showed that shoot regenerated from callus has five different morphologies. This somaclonal variation was permanent after continuously subcultured onto MS medium with no addition of plant growth regulators. Artemisinin was detected using HPLC and it was comfirmed by LC-MS. The results showed that shoot culture type B contained the highest artemisinin content (0.171%) amongst other type of morphology. Shoot type D showed the lowest level of artemisinin (0.006%) which was not significantly different with type E (0.008%). Addition of BAP at concentration of 1 and 2 mg/l increased artemisinin level of the shoot culturs.